2008
DOI: 10.1007/s12040-008-0049-3
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of sedimentation during the Late Paleozoic, Gondwanaland glaciation: An example from the Talchir Formation, Satpura Gondwana basin, central India

Abstract: The Talchir Formation of Permian age is the lowermost lithostratigraphic unit of the Indian Gondwana successions preserving a record of the Late Paleozoic glaciation that affected the whole Gondwanaland. The formation unconformably overlies the Precambrian basement in all the Gondwana basins of India, and marks initiation of sedimentation after a long hiatus since the Proterozoic. The Talchir Formation of the Satpura Gondwana basin of central India shows features diagnostic of deposition under glacial regime s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…Dominance of first-cycle detritus in the Talchir sandstones is evident from abundance of rock fragments from the Precambrian basement complex. Abundance of fresh feldspars and unstable rock fragments, presence of authigenic smectite (McKinley et al, 2003) and virtual absence of epimatrix are generally consistent with reported cold and arid climate of the Talchir period (Chakraborty and Ghosh, 2008).…”
Section: Talchir Formationsupporting
confidence: 83%
See 2 more Smart Citations
“…Dominance of first-cycle detritus in the Talchir sandstones is evident from abundance of rock fragments from the Precambrian basement complex. Abundance of fresh feldspars and unstable rock fragments, presence of authigenic smectite (McKinley et al, 2003) and virtual absence of epimatrix are generally consistent with reported cold and arid climate of the Talchir period (Chakraborty and Ghosh, 2008).…”
Section: Talchir Formationsupporting
confidence: 83%
“…During this movement, the climate changed from cold (glacial), arid (Talchir Formation) to temperate, humid (Barakar Formation), to warm, subhumid/semiarid (Denwa Formation; Ray and Chakraborty, 2002;Ghosh et al, 2004;Chakraborty and Sarkar, 2005;Ghosh et al, 2006;Chakraborty and Ghosh, 2008). Independent sedimentological evidence suggests that there had been cyclical changes in the amount of precipitation with a net warming trend during the Gondwana sedimentation (Suttner and Dutta, 1986;Ghosh et al, 1998).…”
Section: Satpura Gondwana Basinmentioning
confidence: 99%
See 1 more Smart Citation
“…The Permo-Cretaceous Satpura Gondwana succession has been classified into seven major lithostratigraphic unit that form oldest to youngest are the Talchir, Baraker, Motur, Bijori, Pachmarhi, Denwa and Bagra formations (Figures 2 and 3, Table 1). Barring the lowermost glacio-marine and glacio-fluvial deposits, the rest of the succession largely comprises a variety of fluvial deposits with some records of fluvio-deltaic and fluvio-lacustrine sediments [11][12][13][14][15][16].…”
Section: Geological Settingmentioning
confidence: 99%
“…1). The geology of the area has been carried out by many workers viz Medlicott (1873), Jones (1887), Hobson (1926), Fox (1934), Crookshank (1936), Casshyap (1973), Casshyap and Qidwai (1971), Casshyap et al (1993), Rai and Shukla (1979), Shukla and Rai (1977), Raja Rao (1983), Peters and Singh (2001), Ghosh et al (2001), Ray and Chakraborty (2002) Singh and Shukla (2004), Ghosh et al (2004), Chakroborty and Ghosh (2005) and Chakraborty and Ghosh (2008).…”
Section: Introductionmentioning
confidence: 99%